The impact of corruption on development: a comparative developmental perspective - Coetzee, Johannes Jacobus (Nawa: journal of language and communication, 2015)
Corruption has attracted increased and intensive consideration in discourse on development in recent years. Beyond being an ethical problem, corruption is also a governance and development challenge. To contextualise the impact of corruption on development, a comparative analysis of the outstanding development characteristics of developing as opposed to developed countries of 16 internationally accepted indices has been conducted. From analysing the indices, overall patterns emerge that demonstrate that developing countries such as Namibia and Kenya, with relatively low scores in terms of development indicators, present more obstructions to development that act as co-producers of corruption compared to a developed country such as Norway, which has fewer such obstructions. Such co-producers and their interaction increase the level and complexity of corruption as well as magnify its impact on development. As the drivers of corruption take different forms, emerging obstructions are less dominant in developed countries and, given all other possible co-producers, corruption can be managed more easily compared to the situation in developing countries. To change a culture of corruption requires that the environment must be developed to make problems impossible to arise and to dissolve corruption as a complex problem situation. Keywords: Corruption; development; perceptions; co-producers.
Author supplied preprint
Keywords: Corruption; Development; Perceptions; Co-producers